2014
DOI: 10.1002/j.1556-6978.2014.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Research Training in Doctoral Programs Accredited by the Council for Accreditation of Counseling and Related Educational Programs

Abstract: Faculty in 38 doctoral counselor education programs accredited by the Council for Accreditation of Counseling and Related Educational Programs identified the quantitative and qualitative designs and other research topics that were covered in required and elective course work, discipline of course instructors, and opportunities for doctoral students' hands-on research experience. Results indicated a wide range of research training offerings and modest faculty satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 39 publications
(38 reference statements)
2
46
0
Order By: Relevance
“…The ACA (2014) Despite the emphasis on the scientist-practitioner model, the limited research competency among counselors is a persistent issue in the counseling profession (Borders, Wester, Fickling, & Adamson, 2014;Generali et al, 2011;Murray, 2009;Okech, Astramovich, Johnson, Hoskins, & Rubel, 2006;Wester, Borders, Boul, & Horton, 2013 Borders et al (2014) reported that there is a wide range of variation in terms of level, intensity, and quality of research training doctoral students receive. For example, Borders et al (2014) found that among the 60.5% of programs sampled, counselor educators did not teach qualitative research methods content.…”
Section: Journal Of Counselor Preparation and Supervision Volume 9 mentioning
confidence: 99%
See 1 more Smart Citation
“…The ACA (2014) Despite the emphasis on the scientist-practitioner model, the limited research competency among counselors is a persistent issue in the counseling profession (Borders, Wester, Fickling, & Adamson, 2014;Generali et al, 2011;Murray, 2009;Okech, Astramovich, Johnson, Hoskins, & Rubel, 2006;Wester, Borders, Boul, & Horton, 2013 Borders et al (2014) reported that there is a wide range of variation in terms of level, intensity, and quality of research training doctoral students receive. For example, Borders et al (2014) found that among the 60.5% of programs sampled, counselor educators did not teach qualitative research methods content.…”
Section: Journal Of Counselor Preparation and Supervision Volume 9 mentioning
confidence: 99%
“…This means that different treatments for similar issues may differ drastically depending on a person's cultural milieu. This requires counseling professionals to be versatile in the approaches utilized to treat individuals, which further complicates matters in regard to how to best train counseling students to be competent consumers and producers of research (Dukic, 2015;Generali, Foss-Kelly, & McNamara, 2011;Wester & Borders, 2014).…”
Section: Journal Of Counselor Preparation and Supervision Volume 9 mentioning
confidence: 99%
“…Despite the emphasis on the scientist-practitioner model, the limited research competency among counselors is a persistent issue in the counseling profession (Borders, Wester, Fickling, & Adamson, 2014;Generali et al, 2011;Murray, 2009;Okech, Astramovich, Johnson, Hoskins, & Rubel, 2006;Wester, Borders, Boul, & Horton, 2013). For example, Okech et al (2006) found that counselor educators in CACREP-accredited doctoral counselor education programs possessed varying levels of research training competence, which likely reflects the inconsistent and varied research training doctoral students receive.…”
mentioning
confidence: 99%
“…For example, Okech et al (2006) found that counselor educators in CACREP-accredited doctoral counselor education programs possessed varying levels of research training competence, which likely reflects the inconsistent and varied research training doctoral students receive. More recently, Borders et al (2014) reported that there is a wide range of variation in terms of level, intensity, and quality of research training doctoral students receive. For example, Borders et al (2014) found that among the 60.5% of programs sampled, counselor educators did not teach qualitative research methods content.…”
mentioning
confidence: 99%
See 1 more Smart Citation